2015
DOI: 10.5530/pj.2015.5.10
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Antimalarial Evaluation of Embelin and its Semi-Synthetic Aromatic Amine Derivatives

Abstract: Background: In less developed countries like Ethiopia, malaria is traditionally treated by remedies prepared from medicinal plants. One such plant that falls in this category is Embelia schimperi Vatke whose fruits are employed for the treatment of a variety of ailments including taeniasis and malaria. Objective: In the present study, the in vivo antimalarial activity of embelin isolated from the fruits of Embelia schimperi Vatke and its semisynthetic aromatic amine derivatives was evaluated. Methods: Silica g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Knowing the importance of the anti-inflammatory potential of embelin, in 2014, Mahendran et al reported the synthesis of embelin analogs as anti-inflammatory agents [9] . Later, Bezu et al reported phenazine derivative of embelin as an analgesic and anti-inflammatory agent [10] . Further, Vault et al reported the synthesis and anti-inflammatory activity of mono, di-acetyl embelin prepared in one step.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the importance of the anti-inflammatory potential of embelin, in 2014, Mahendran et al reported the synthesis of embelin analogs as anti-inflammatory agents [9] . Later, Bezu et al reported phenazine derivative of embelin as an analgesic and anti-inflammatory agent [10] . Further, Vault et al reported the synthesis and anti-inflammatory activity of mono, di-acetyl embelin prepared in one step.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on anticancer potential of embelin were reported by Mishra et al [21]. The aromatic amine derivatives of Embelin were reported to exhibit antimalarial activity [22]. This herbal medicine is thus gaining popularity in the recent years mainly due to its natural abundance and multifaceted activities.…”
mentioning
confidence: 99%